Perhatian Media dan Penghindaran Pajak: Studi Kasus Perusahaan LQ45 yang Terdaftar di BEI Tahun 2020-2022 - Kharisma, Leni; Cheisviyanny, Charoline (Universitas Negeri Padang, 2025)
This study aims to examine the effect of media attention on corporate tax avoidance. This research is an associative type with a quantitative approach. The population includes LQ45 companies listed on the Indonesia Stock Exchange in 2020-2022. The sampling technique was carried out using purposive sampling method, there were 97 companies from 2020 to 2022 which became the sample of this study. The tax avoidance variable as the dependent variable is measured by Current ETR. Media attention as one of the independent variables, measured by summarizing the number of articles from issuers that appear in the headlines. Then, news representing different emotions will be further summarized with negative = 1, neutral = 2, and positive = 3. The simultaneous test results show that the independent variables jointly affect the dependent variable. However, partially, only positive media attention has a negative and significant effect on corporate tax avoidance.